Metabolic control of circulation. Effects of iodoacetate and fluoroacetate. - Liang, C S (1977)
The circulatory effects of selective metabolic inhibition of glycolysis and of the tricarboxylic acid cycle by iodoacetate and fluoroacetate were studied in intact chloralose-anesthetized dogs. Pulmonary arterial blood pressure and vascular resistance increased after administration of both inhibitors, but neither systemic hemodynamics nor myocardial contractility changed significantly. Coronary blood flow did not change after iodoacetate administration but increased four- to five-fold after fluoroacetate. Administration of normal saline had no effect on any of the parameters. The changes in pulmonary arterial blood pressure and coronary blood flow after fluoroacetate were not mediated via the autonomic nerves or adrenergic neurohumors because they still occurred after autonomic nervous system inhibition. Neither myocardial oxygen consumption nor left ventricular work changed. A selective increase in myocardial blood flow also occurred in conscious dogs after fluoroacetate administration; hepatic artery flow was reduced, but other organ flows did not change significantly. These results indicate that pulmonary pressor and coronary dilator effects may be produced in intact dogs by selective metabolic blockade, in the absence of reduced oxygen supply or impairment in the electron transport system. These results also suggest that the increases in pulmonary arterial blood pressure, coronary blood flow, and cardiac output that occur during hypoxia probably are related to separate metabolic events in the tissue.